Richard Mollica, Md, Mar. Textbook of global mental health: trauma and recovery - Perales Cabrera, Alberto (2014)
This is to communicate on the book by Richard Mollica. Md, sea. Text Global Mental Health: Trauma and Recovery. Guidelines for clinical care and field trauma victims worldwide (Textbook of global mental health. Trauma and recovery A companion guide for field and clinical care of traumatized people worldwide). Edited by Harvard Refugee Trauma Program, USA, 2011m electronic version can be obtained for $ 60.00 with: http: // mollica/ www.lulu.com/shop/richard-f-textbook-of-global-mind-healthtrauma- and companionguide- -recovery-for-a-field-and-clinical-care-people-worldwide oftraumatized- / ebook / product-16599951.html.